2021
DOI: 10.3390/vaccines9101076
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Relevance of the Microbiome in Hidradenitis Suppurativa: A Systematic Review

Abstract: Hidradenitis suppurativa is a chronic disease of the pilosebaceous unit. The name of the condition is a testament to the presumed relationship between the disease and the microbiome. The pathophysiology of hidradenitis suppurativa is, however, complex and believed to be the product of a multifactorial interplay between the interfollicular epithelium, pilosebaceous unit, microbiome, as well as genetic and environmental factors. In this review we assimilate the existing literature regarding the role played by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 136 publications
0
18
0
Order By: Relevance
“…Persons with HS also had a significant reduction in Faecalibacterium prausnitzii and increased abundance of E. coli in their gut. 15 , 213 , 214 …”
Section: Methodsmentioning
confidence: 99%
“…Persons with HS also had a significant reduction in Faecalibacterium prausnitzii and increased abundance of E. coli in their gut. 15 , 213 , 214 …”
Section: Methodsmentioning
confidence: 99%
“…Potentially, the altered microbiome promotes chronic inflammation by triggering the innate lymphoid cell population in an IL-17R dependent manner ( Sakamoto et al, 2021 ). These findings may partly underpin the dysregulated cutaneous microbiome that accompanies HS ( Mintoff et al, 2021a ). Murine models have also demonstrated that disruption of notch nuclear target RBP-J results in cyst formation and epidermal hyperkeratinization ( Yamamoto et al, 2003 ).…”
Section: Discussionmentioning
confidence: 98%
“…The pathophysiology of HS is complex and is strongly determined by environmental and lifestyle factors such as smoking and obesity. These factors interact with specific physical triggers, namely friction, sweat, increased temperature, and changes in the cutaneous microbiome to drive disease risk ( Mintoff et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…The balance between commensal microbiota contributes to, and is a hallmark of cutaneous homeostasis ( 15 ). In contrast, microbial dysbiosis is a well-established feature of HS ( 16 , 17 ). Compared to other skin loci, intertriginous areas affected in HS have a high density of pilosebaceous-apocrine units, higher temperature and moisture, but lower oxygen availability all contributing to specific microbiome composition and increased risk of dysbiosis ( 1 , 2 , 5 , 18 ).…”
Section: Microbial Dysbiosis In Hsmentioning
confidence: 99%